An analysis of Abraham Maslow’s hierarchy of needs theory and Frederick Herzberg’s work motivation theory - Tika Dwi Aprilia; Siti Komariah; Nopi Irawan; Sutarto Sutarto (The Future of Education Journal, 2025)
This mini-research examines two of the most influential motivation theories in the study of human and organizational behavior, namely Abraham Maslow’s Hierarchy of Needs Theory and Frederick Herzberg’s Two-Factor Theory. This study aims to analyze the basic concepts, assumptions, relevance, criticisms, and practical implications of both theories within the context of modern organizations. The method employed is a literature review (library research) by examining classic books, scholarly articles, and human resource management literature. The findings indicate that Maslow views motivation as the fulfillment of hierarchical needs, while Herzberg distinguishes between factors that lead to satisfaction (motivators) and dissatisfaction (hygiene factors). Both theories have strengths and limitations, yet remain relevant for human resource development, leadership, job design, and employee retention strategies.